An impaired learning environment: Resident physicians’ experience of the transition to pandemic care during the first wave of the COVID-19 pandemic in Sweden - Brulin, Emma; Henriksson, Kristina; Landstad, Bodil J. (Frontiers in Psychology, 2023)
Extensive studies regarding the COVID-19 pandemic have shown negative effects on physicians-in-training. Besides a high workload, their learning environment has been affected. A quality learning environment is vital for residents' physician's clinical development and also their health. Nevertheless, few studies have explored this. The aim of this study was to explore resident physicians' experiences of the transition to pandemic care during the first wave of the COVID-19 pandemic in Sweden. In this qualitative study, 12 Swedish resident physicians were interviewed using a semi-structured interview guide. They were interviewed between June and October of 2020 and asked to reflect on the pandemic and, more specifically, the first wave. The empirical material was analysed using qualitative content analysis. The analysis resulted in one theme and four categories. The theme identified was An impaired learning environment which signifies the disruptions the resident physicians experienced during the first wave of the pandemic. The four categories, Professional role insecurity, High expectations but little influence, Stagnant clinical development, and Professional growth through experience, describe in what way the learning environment was impacted.